2020
DOI: 10.1002/chem.202001510
|View full text |Cite
|
Sign up to set email alerts
|

Multinuclear PtII Complexes: Why Three is Better Than Two to Enhance Photophysical Properties

Abstract: The self‐assembly of platinum complexes is a well‐documented process that leads to interesting changes of the photophysical and electrochemical behavior as well as to a change in reactivity of the complexes. However, it is still not clear how many metal units must interact in order to achieve the desired properties of a large assembly. This work aimed to clarify the role of the number of interacting PtII units leading to an enhancement of the spectroscopic properties and how to address inter‐ versus intramolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 64 publications
5
18
0
Order By: Relevance
“…Additionally, a hypsochromic shift in the emission spectra with a new emission maximum at 590 nm was recorded, attributable to modified Pt···Pt-interactions present in this aggregate (Figure S2). Interestingly, when OSCs are not present, the aggregates are stable in solvent compositions having a dioxane content up to 28%, which is in agreement with what was previously reported and observed for the reference solution, in which the platinum aggregates dissolved and evolved toward the thermodynamic stable supramolecular aggregates. Remarkably, we found that the entrapped species ( Pt AC @OSCs ) withstand dissolution in solvent compositions containing up to 37% dioxane, reflecting the increased stability of these aggregates due to their confinement in the nanocontainers.…”
Section: Results and Discussionsupporting
confidence: 91%
“…Additionally, a hypsochromic shift in the emission spectra with a new emission maximum at 590 nm was recorded, attributable to modified Pt···Pt-interactions present in this aggregate (Figure S2). Interestingly, when OSCs are not present, the aggregates are stable in solvent compositions having a dioxane content up to 28%, which is in agreement with what was previously reported and observed for the reference solution, in which the platinum aggregates dissolved and evolved toward the thermodynamic stable supramolecular aggregates. Remarkably, we found that the entrapped species ( Pt AC @OSCs ) withstand dissolution in solvent compositions containing up to 37% dioxane, reflecting the increased stability of these aggregates due to their confinement in the nanocontainers.…”
Section: Results and Discussionsupporting
confidence: 91%
“…The emission of Pt-3OC 12 H 25 and Pt-3OC 16 H 33 in aggregation peaks at 588 and 592 nm, respectively, gives rise to yellow color to their powder. These yellow color emissions can be ascribed to the MMLCT that is boosted by the Pt···Pt and π–π stacking interactions. , These Pt···Pt interactions can be verified by the newly generated intense emission peaked at 580 nm when increasing the complex concentration (Figure S31), in consistency with the reports from Che, Yam, De Cola, Wang and co-workers. Excitingly, these LLCs in aggregation exhibit a high QY, that is, 88% for Pt-3OC 12 H 25 and 83% for Pt-3OC 16 H 33 , respectively. Besides, they show a relatively long photoluminescence lifetime, that is, 443 and 467 ns, respectively (Figure S32).…”
Section: Resultssupporting
confidence: 85%
“…In addition to complexes 1-4, complex 5 (Figure S4.1) was also included, as it is offers an example of a derivative of 1 that displays blue-shifted excimer emission relative to the parent and thus offers an opportunity to cross-check the reliability of the modelling. 44 Since metallophilic Pt-Pt interactions have generally been considered central to the formation of excimers or aggregates of Pt(II) complexes, 7,12,32,55,56 our model comprises molecules disposed parallel to each other and with the metal centres positioned on the z-axis (Figure 10). Given the C 2 symmetry of the complexes 1-5 in the ground state, we have considered two possible starting geometries: one with the ancillary chloride ligands on the same side (a head-to-head arrangement or syn, and the other with the chlorides on opposite sides (head-to-tail or anti).…”
Section: Dft and Td-dft Calculationsmentioning
confidence: 99%